Pengendalian Kadar Gula Darah Pasien Diabetes Mellitus Tipe 2 Melalui Telehealth - Nurwahidah Nurwahidah; Wahyu Dini Candra Susila; Abu Bakar; Harmayetty Harmayetty; Siti Nur Qomariah (FORIKES, 2024)
In today's era, telehealth technology is one of the things that continues to develop to support the effectiveness of work, in this case for the treatment process. Telehealth is used to fulfill nursing care for patients who are constrained by distance. Telehealth is also widely used in patients with type 2 diabetes mellitus. This study aimed to determine the effectiveness of telehealth in achieving blood glucose stability in patients with type 2 diabetes mellitus. This systematic review searched for relevant articles using keywords based on MeSH in the Scopus, ScienceDirect, PubMed, and ProQuest databases. The study guidelines used were PRISMA. The literature search was conducted on studies from 2018 to 2023, in English and full text. The keywords used in the article search were